International Monetary Fund Annual Report 1983. (Annual Report of the Executive Board; Annual Report of the Executive Board ;, 1983)
This paper reviews the IMF's Annual Report for the fiscal year ended April 30, 1983. The report highlights that the recession in economic activity intensified in most parts of the world during 1982. At the same time, however, further progress in curbing inflation was recorded in several of the major industrial countries. This progress had favorable implications for the real incomes of consumers, and the accompanying decline in interest rates improved business incentives and reduced inventory carrying costs.